ASSOCIATION BETWEEN CENTRAL OBESITY PARAMETERS AND BLOOD PRESSURE PHENOTYPES: STUDY AMONG WOMEN. - PALLAVI S. KANTHE,; BHEEMSHETTY S PATIL,; GOUHAR BANU SHAIKH, (International Journal of Pharma and Bio Sciences, 2015)
A cross sectional study of 138 women in the age group of 26- 35 years was conducted to study the relationship between central obesity and blood pressure phenotypes. According to BMI measurements, subjects were divided into three groups namely: Normal weight (Group1) –BMI 18.5-24.9 kg / m2, Overweight (Group2) - 25 kg / m2 - 29.9 kg / m2, Obese (Group3) - BMI≥ 30 kg / m2). BMI, WHR, WHtR, BP phenotypes like SBP, DBP, PP and MAP were recorded. Results showed insignificant increase in blood pressure phenotypes with increasing BMI, WHR and WHtR in groups II and III compared to group I. BMI and WHR showed significant positive correlations with both SBP and PP. WHtR had showed significant positive correlation with SBP. BMI, WHR and WHtR have some independent effect on the risk of elevated blood pressures among females. WHR and BMI were found to be equally important indicator to predict the risk of cardiovascular diseases.